Evaluation of Special Economic Zone Policy and Suggestions for Vitalization of Free Economic Zone - Yeongkwan Song (Korea Development Institute (KDI), 2015)
The competition among countries to attract anchor businesses with significant economic ripple effects is intensified each day. In this regard, the current eight Free Economic Zones must be reduced in number in order to enhance their competitiveness and they must serve as 'new testing ground for regulations' so as to facilitate differentiation from Free Economic Zones of competing countries. - The government has maintained special economic zone policy to boost foreign investment, but questions have been raised about its effectiveness. - In eight free economic zones, the proportion of undeveloped land is close to half the total land area of designated areas. For example, in Donghae-Yulchon Free Economic Zone, the occupancy rate is even less than 30%. - The number of foreign-invested firms located in special economic zones account for less than 4% of the total and in the case of free economic zones, more than 90% of its occupants are domestic firms. - There is little factual evidence which suggests that foreign-invested firms located in special economic zones outperform domestic firms. - As locational considerations, foreign investors consider market accessibility and infrastructure to be of paramount importance. Nonetheless, the locational competitiveness of Korea's free economic zone is not superior to that of its competitors such as China, Hong Kong and Singapore. - The locational disadvantage of free economic zone should be overcome by recruiting a pool of professionals, but Korea faces difficulties in this regard. - Korea has to redefine its policy goal for free economic zone as 'testing ground for regulation,' and revoke the designation of several free economic zones whose policy goal is hard to achieve. Thereafter, it should reestablish the revoked zones as high-tech innovation complex or foreign investment zones. - In order to vitalize foreign investment, focus should be shifted from quantity to quality; the country's foreign investment management system which oversees and supports attraction of foreign investment should be enhanced in terms of its professionalism, and policies to attract foreign investment should become more flexible.
Keywords: 330